AGE OF BREEDER AND VITAMIN SUPPLEMENTATION ON THE BROILERS’ PERFORMANCE - LIMA, Nilsa Duarte da Silva; GARCIA, Rodrigo Garófallo; NÄÄS, Irenilza DE ALENCAR; CALDARA, Fabiana Ribeiro (Revista Brasileira de Engenharia de Biossistemas, 2012)
The aim of the study was to evaluate the effect of vitamin supplementation in the first week of life on the performance of broiler-hacking from arrays of different ages. 2,592 day-old chicks from Cobb genetic strain were housed in a completely randomized design, distributed in an arrangement of 2x3 factorial, two breeders ages (29 and 44 weeks) and three levels of included vitamins (without vitamins, level recommended by the manufacturer and 50% higher than that of the commercial) with eight replicates per treatment. Data analysis were done using PROC GLM of SAS and compared by Tukey test at 95% probability. Vitamin A supplement did not influence the performance of the birds in the first week and at 42-days old. There was age-influenced in breeder mean weight gain, final mean weight and average feed consumption during the first week of bird life. The use of the vitamin complex can be recommended in case of constraints such as nutritional disability of breeders and health aspects that can affect the birds’ performance.